2022
DOI: 10.3390/ijms232113039
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin Treatment Silences Epithelial–Mesenchymal Transition Involved in Pulmonary Fibrosis in a Murine Model of Hypersensitivity Pneumonitis

Abstract: Pulmonary fibrosis is becoming an increasingly common pathology worldwide. Unfortunately, this disorder is characterized by a bad prognosis: no treatment is known, and the survival rate is dramatically low. One of the most frequent reasons for pulmonary fibrosis is hypersensitivity pneumonitis (HP). As the main mechanism of pulmonary fibrosis is a pathology of the repair of wounded pulmonary epithelium with a pivotal role in epithelial–mesenchymal transition (EMT), we assumed that EMT silencing could prevent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Snail1/RhoA/α-SMA pathway is a proven mechanism involved in fibroblast activation [ 12 ], and several studies have demonstrated that Snail1 participated in organ fibrosis, i.e., renal fibrosis, cardiac fibrosis, and lung fibrosis [ 10 , 22 , 23 ]. On the basis of these observations, the role of Snail1 in FBXL8-regulated myofibroblast differentiation is to be investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Snail1/RhoA/α-SMA pathway is a proven mechanism involved in fibroblast activation [ 12 ], and several studies have demonstrated that Snail1 participated in organ fibrosis, i.e., renal fibrosis, cardiac fibrosis, and lung fibrosis [ 10 , 22 , 23 ]. On the basis of these observations, the role of Snail1 in FBXL8-regulated myofibroblast differentiation is to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Snail1 is a zinc finger transcription factor, which is not normally expressed in adult fibroblasts, but highly expressed in myofibroblasts [ 11 ]. Substantial evidence has proved that Snail1 plays a crucial role in EMT and is associated with organ fibrosis, such as lung and renal fibrosis [ 22 , 23 ]. Recently, Stanisavljevic et al provided additional insight into the role of Snail1 in CFs activation, and Snail1-deleted fibroblast failed to gain myofibroblast characteristics, such as α-SMA expression and collagen secretion [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Injured epithelial cells or cells can acquire migration capacity similar to that of mesenchymal cells through epithelial‐mesenchymal transition (EMT)/endothelial‐mesenchymal transition (EndoMT), and subsequently differentiate into MFBs. In addition, circulating fibroblast‐like cells and mesenchymal stem cells (MSCs) both show the capacity to transdifferentiate into MFBs [23].…”
Section: Introduction To Pathological Mechanisms Of Rifmentioning
confidence: 99%